Updated management surgical treatment of esophageal cancer: Manejo actualizado en el tratamiento quirúrgico del cáncer de esófago - Jáuregui-Francia, Filomeno Teodoro (2018)
Introduction: Surgical treatment of esophageal cancer remains a challenge despite advances in surgical technique, pre-operative care, postoperative care and postoperative complications. Objective: diagnosis and updated management in the surgical treatment of cancer in the national hospital Edgardo Rebagliati Martins - EsSalud. Methods: Patients diagnosed with esophageal cancer who were admitted to the surgery service at the Edgardo Rebagliati Martins - EsSalud national hospital during 2017 were selected. Patients of both sexes were included, starting at 20 years of age. . For the selection of the sample, it was stratified by age and sex according to the diagnosis of esophageal cancer. Results: Fourteen patients with esophageal cancer were diagnosed by means of the clinical history, laboratory exams, endoscopy with biopsy, cervical abdominal thoracic tomography, and contrasted duodenum stomach esophagus radiography. No patient was found less than 40 years old, predominantly male, in the age group between 61 and 80 years of age, all showed dysphagia, odynophagia and weight loss, the most frequent post-operative complication was the fistula of the cervical anastomosis. Conclusion: Fourteen patients with esophageal cancer, esophagectomy and the restoration of gastrointestinal tract continuity were diagnosed. Anastomotic leaks and pulmonary complications are the main causes of morbidity and mortality after an esophagectomy. DOI 10.25176/RFMH.v18.n4.1732